Farming of cobia, Rachycentron canadum (Linnaeus 1766) in open sea floating cages in India - Philipose, K. K.; Loka, Jayasree; Krupesha Sharma, S. R.; Divu, D.; Srinivasa Rao, K.; Sadhu, Narasimhulu; Dube, Praveen; Gopakumar, G.; Syda Rao, G. (Indian Journal of Fisheries, 2013)
Experiments on culture and growth performance of cobia were undertaken in marine cages installed in the Arabian Sea off Karwar on the south-west coast of India. Hatchery produced cobia fingerlings were stocked at two densities of 3.5 fish cubic m-1 and 14.1 fish cubic m-1 in circular HDPE cages. Mean weight and specific growth rate (SGR) of cobia stocked @ 3.5 fish cubic m -1 were 10.5 kg and 2.2% day-1, respectively, at 300 days of culture (DOC). Cobia stocked @ of 14.1 fish cubic m-1 attained an average weight of 3.68 kg and SGR of 1.9% day-1 at 300 DOC. SGR was found to be positively correlated with water temperature and salinity during the culture period. No significant variation was found in SGR and feed conversion ratio of cobia stocked at two different densities. However, absolute growth rate, relative growth rate and mean weight of cobia varied significantly between the two groups.